Pengaruh Gaya Mengajar Resiprokal Terhadap Kemampuan Gerak Dasar Pada Servis Pendek Backhand Dalam Permainan Bulu Tangkis Pada Peserta Didik Kelas VIII Di SMP Negeri 1 Tombulu - Gyrellhio F.M Udung; Mesak A.S.F Rambitan; Edita A.M Pinangkaan (STIKES Columbia Asia Medan, 2025)
The problem in this study is whether the influence of reciprocal force exerts an influence on the basic movement ability on the backhand short serve in grade VIII learners at SMP Negeri 1 Tombulu. The purpose of this study was to test the mean score of basic movement skills on backhand short serve in grade VIII learners at SMP Negeri 1 Tombulu. The research method used was experimental method. This study is a quantitative study. The research instrument used was Basic Movement Ability Test On Backhand Short Serve In Badminton Game. From the research results that have been proven through statistical data analysis the effect of reciprocal force on basic movement in short backhand service in badminton game has a significant effect. It can be seen from tcount is greater than ttable, namely tcount = 4.18 > ttable = 2.086. Based on the testing criteria, if tcount is greater than ttable (tcount > ttable), then H0 is rejected, which means HA is accepted. Thus the conclusion of the test is the average basic movement ability in short backhand service in badminton game of the experimental group taught with reciprocal style is better than the average basic movement ability in short backhand service in badminton game of the control group that did not receive treatment.